Impact of tocilizumab on mortality and/or invasive mechanical ventilation requirement in a cohort of 206 COVID-19 patients. (October 2020) - Klopfenstein, Timothée; Zayet, Souheil; Lohse, Anne; Selles, Phillippe; Zahra, Hajer; Kadiane-Oussou, N'dri Juliette; Toko, Lynda; Royer, Pierre-Yves; Balblanc, Jean-Charles; Gendrin, Vincent; Conrozier, Thierry; ,
Highlights: No therapeutics have yet been proven effective for the treatment of severe illness caused by SARS-CoV-2. By neutralizing a key inflammatory factor in the cytokine release syndrome in COVID-19, tocilizumab (TCZ) can block the cytokine storm and reduce the severity of the disease. Our case-control study found that patients treated with TCZ had a lower index of mortality and/or invasive mechanical ventilation (IMV) requirement than patients without TCZ. This result strongly suggests that TCZ may reduce the number of IMV requirements and/or mortality in patients with severe SARS-CoV-2 pneumonia. This idea needs to be confirmed and spread in the medical community. Abstract: Introduction: No therapy has proven to be effective yet to reduce mortality and/or invasive mechanical ventilation (IMV) requirement in COVID-19. Tocilizumab (TCZ) in patients with severe COVID-19 could be an effective treatment. Methods: We conducted a retrospective case-control study in the Nord Franche-Comté Hospital, France. We compared the outcome of patients treated with TCZ and patients without TCZ considering a combined primary endpoint: mortality and/or IMV requirement. Results: Thirty patients were treated with TCZ and 176 patients were treated without TCZ. TCZ was used in patients in critical condition (oxygen therapy flow at TCZ onset was 10.5 L/min and 14/30 patients had ≥ 50% lung involvement on CT scan) as a rescue treatment (8/30 patients who died were not admitted in USC in regard to their comorbidities). However, mortality and/or IMV requirement were lower in patients with TCZ than in patients without TCZ (27% vs 52%, p = 0.009). Conclusion: Despite the small sample size in the TCZ group, this result suggests that TCZ reduces mortality and/or IMV requirement in patients with severe SARS-CoV-2 pneumonia. This notion needs to be confirmed and spread in the medical community.